Developing Performance-Based Teaching Materials to Support Lesson Planning Competence of Preservice Science Teacher - Alwan Mahsul; Lalu Muktar (Universitas Pendidikan Mandalika, 2025)
Preservice science teachers frequently struggle to design coherent lesson plans that align learning objectives, teaching methods, and assessment with current policy demands such as Merdeka Belajar Kampus Merdeka and the Indonesian National Qualifications Framework. This study aimed to develop, validate, and conduct a limited trial of performance-based teaching materials for a Science Instructional Design course, consisting of student worksheets and a textbook structured with the Kemp instructional design model. A design and development approach was employed, followed by a small-scale field implementation with one cohort in a science education program at an Islamic university. Data were collected through expert validation sheets addressing format, language, and content; a readability test with six students of high, medium, and low achievement; a performance rubric for lesson planning (competency analysis, indicator development, lesson plan construction, method selection); and student questionnaires on interest and motivation. Data were analyzed descriptively. The materials were rated valid to highly valid by experts, with high inter-rater agreement. Readability indices indicated that the textbook was easy to understand, with an average difficulty of about 5.5 percent. Most students achieved good to excellent ratings on competency analysis, indicator development, and lesson plan structure, while performance in method selection remained relatively weak. Student responses showed good interest and very good motivation, particularly in confidence to prepare lesson plans. Given the single-group, single-institution design and absence of a comparison group, the findings indicate feasibility and promise rather than demonstrated effectiveness in improving lesson-planning competence.